2020
DOI: 10.1016/j.stem.2020.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-Linked Kinase Mediates Therapeutic Resistance of Quiescent CML Stem Cells to Tyrosine Kinase Inhibitors

Abstract: Highlights d The composition of focal adhesions mediating niche interactions is altered in LSCs d ILK is a focal adhesion component required for LSC selfrenewal in vivo d ILK inhibition sensitizes therapy-resistant patient LSCs to standard chemotherapy d The mitochondrial metabolism of quiescent LSCs is perturbed by ILK inhibition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 69 publications
0
34
0
Order By: Relevance
“…Regarding regulation of the tricarboxylic acid (TCA) cycle and OxPHOS, a comparative gene expression analysis in CML stem-progenitor cells isolated from TKI-responding and non-responding patients revealed upregulation of ILK (integrin-linked kinase) in LSCs of non-responding patients [ 152 ]. It was shown that ILK regulates quiescence of non-responding LSCs through the OxPHOS pathway [ 152 ]. The multifunctional sirtuin 1 (SIRT1) was also found to be induced in CML-LSCs and contributes to their resistance to TKIs [ 153 ].…”
Section: Molecular Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding regulation of the tricarboxylic acid (TCA) cycle and OxPHOS, a comparative gene expression analysis in CML stem-progenitor cells isolated from TKI-responding and non-responding patients revealed upregulation of ILK (integrin-linked kinase) in LSCs of non-responding patients [ 152 ]. It was shown that ILK regulates quiescence of non-responding LSCs through the OxPHOS pathway [ 152 ]. The multifunctional sirtuin 1 (SIRT1) was also found to be induced in CML-LSCs and contributes to their resistance to TKIs [ 153 ].…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Kumar et al (2020) showed that BCR-ABL1 T315I mutated cells presented alteration in the actin cytoskeleton, integrin β3 levels, in the expression and phosphorylation levels of FAK and ILK, and fibronectin expression when compared with BCR-ABL1 sensitive cells [ 194 ]. In CML, the increased expression of integrin β3 and ILK interaction with β integrins was associated with Imatinib resistance through the activation of PI3K/AKT, STAT3, and ERK1/2 signaling pathways [ 152 ]. Furthermore, the interaction with MSCs can also be mediated by N-cadherin and the activation of β-catenin signaling, which are crucial for LSC [ 195 ].…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Importantly, GSEA indicated that QLT0267 repressed expression of mitochondrial OXPHOS-related genes in quiescent CML stem cells. These data establish that ILK has a critical function in regulating the quiescence of TKI-insensitive CML stem cells through the OXPHOS pathway [25].…”
Section: Ilkmentioning
confidence: 53%
“…Rothe et al compared gene expression profiles between human CML stem/progenitor cells isolated from TKIresponder and TKI-non-responder patients, and found that ILK (Integrin-linked kinase) mRNA was elevated in TKIinsensitive CML stem/progenitor cells compared to TKIsensitive CML stem/progenitor cells [25]. To understand the functional role of ILK, they introduced shRNA targeting ILK mRNA into CML stem/progenitor cells from CP-CML patients, and transplanted these ILK-shRNA-transduced CML stem/progenitor cells into immunodeficient NRG mice.…”
Section: Ilkmentioning
confidence: 99%
“…Even the second generation TKIs nilotinib and dasatinib are not effective at eradicating quiescent CML LSCs 15,16 . CML LSCs share many features with normal HSCs, such as the quiescent state, localization in the hypoxia niche, and selfrenewal ability 17,18,19,20,21 . Their quiescent state is one of the major reasons why CML LSCs are resistant to BCR-ABL1 TKIs 22,23 .…”
Section: Introductionmentioning
confidence: 99%